Thermal conductivity of suspended few-layer MoS2. Issue 6 (10th January 2018) - Aiyiti, Adili; Hu, Shiqian; Wang, Chengru; Xi, Qing; Cheng, Zhaofang; Xia, Minggang; Ma, Yanling; Wu, Jianbo; Guo, Jie; Wang, Qilang; Zhou, Jun; Chen, Jie; et al.
Abstract : Thermal conductivity can be continuously tuned to a required value from crystalline to amorphous limits with a clear crystalline–amorphous transition. Abstract : Modifying phonon thermal conductivity in nanomaterials is important not only for fundamental research but also for practical applications. However, the experiments on tailoring thermal conductivity in nanoscale, especially in two-dimensional materials, are rare due to technical challenges. In this work, we demonstrate the in situ thermal conduction measurement of MoS2 and find that its thermal conductivity can be continuously tuned to a required value from crystalline to amorphous limits. The reduction of thermal conductivity is understood from phonon-defect scattering that decreases the phonon transmission coefficient. Beyond a threshold, a sharp drop in thermal conductivity is observed, which is believed to be due to a crystalline–amorphous transition. Our method and results provide guidance for potential applications in thermoelectrics, photoelectronics, and energy harvesting where thermal management is critical with further integration and miniaturization.